Emergency cesarean section rate in the women aged 35 or older compared to those aged 21-25 at Siriraj Hospital - Apiradee Jirattigalachote; Japarath Prechapanich (The Royal Thai College of Obstetricians and Gynaecologists, 2008)
ObjectivesTo compare the emergency cesarean section rate and other pregnancy outcomes in the women aged ≥ 35 with those aged 21-25. DesignRetrospective study. SettingA medical teaching hospital. Subjects200 pregnant women aged ≥ 35 (study group) and 200 pregnant women aged 21-25 (comparison group) who delivered between July 1, 2005 and August 31, 2005. Main outcome measures Demographics, antepartum, intrapartum and postpartum complications including neonatal outcomes. Results The study group had significant increase in rate of cesarean section (55.5% vs 22%, RR 2.5, 95% CI 1.9-3.4). The rate of primary emergency cesarean section in the study group was higher than the comparison group (nullipara 50% vs 20.7%, RR 2.4, 95% CI 1.6-3.6; multipara 14.2% vs 7.3%, RR 2.0, 95% CI 0.7-5.5). Other pregnancy outcomes in both groups were not significantly differrent. Conclusions Advanced maternal age had significantly higher rate of primary emergency cesarean sections compared with the pregnant women aged 21-25.